2010
DOI: 10.4322/actalb.02201008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a plankton community in a fish farm

Abstract: The overall objective of organic and inorganic fertilizers is to increase fish farm productivity. A common practice in fish farms is the fertilization of ponds to enhance algae growth and promote the production of zooplankton suitable for larvae. Several studies carried out in freshwater environments have established that the growth of phytoplankton may be controlled to a large degree by the limitation of nutrients, availability of light and the composition and abundance of zooplankton (Basualto et al., 2006).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Many studies have been conducted on the effects of cage systems on water quality, suspended matter, bottom sediment, plankton, periphyton, and benthic communities. The results were highly variable from system operating causing no changes on the lake conditions (Hakanson et al 1998;Costello et al 2004); to others producing short-term and localized effects (Cornel and Whoriskey 1993); or still other systems significantly impacting water quality, sedimentation rates, and phytoplankton and benthic communities (Stirling and Dey 1990;An and Kim 2003;Guo and Li 2003;Figueredo and Giane 2005;Alves and Baccarin 2006;Tavares et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Many studies have been conducted on the effects of cage systems on water quality, suspended matter, bottom sediment, plankton, periphyton, and benthic communities. The results were highly variable from system operating causing no changes on the lake conditions (Hakanson et al 1998;Costello et al 2004); to others producing short-term and localized effects (Cornel and Whoriskey 1993); or still other systems significantly impacting water quality, sedimentation rates, and phytoplankton and benthic communities (Stirling and Dey 1990;An and Kim 2003;Guo and Li 2003;Figueredo and Giane 2005;Alves and Baccarin 2006;Tavares et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…The values of total alkalinity were 124.02±10.1, 125.97±11.9, 127.07±12.5 and 129.81±14 for T 1 , T 2 , T 3 and T 4 respectively. The pattern of the constant increasing trend of plankton in the treated ponds during the study period confirmed the role of water temperature and photoperiod (Tavares et al, 2010), pH and total alkalinity (Prithwiraj et al, 2008). NO 3 -N and PO 4 -P-status of pond water (Freid et al 2003) and DO (Gormaz et al, 2014) in production profile and total plankton production.…”
Section: Discussionmentioning
confidence: 71%
“…Investigations of zooplankton community in fish farm systems are important tools to evaluate the success of aquaculture ecosystem (Tavares et al, 2010;and Ssanyu et al, 2011). On the other hand, fish density and nutrient supply are the two major factors affecting plankton communities in aquaculture ponds (Mitra et al, 2007).…”
Section: Planktonmentioning
confidence: 99%
“…Many authors found that rotifers and copepods configured the main bulk of zooplankton communities in marine (Case et al, 2008) or freshwater ecosystem (Ssanyu et al, 2011), regardless to the type of cultured water, cultured fish, water quality and geographical location. However, the structure and functioning of the zooplankton community, regarding to species compositions and densities of each species, are affected by several factors, such as (1) water quality aspects, (2) nutrient limitation, (3) phytoplankton (availability, species and community structure) and (4) predator types and densities (Tavares et al, 2010 andSsanyu et al, 2011).…”
Section: Planktonmentioning
confidence: 99%
See 1 more Smart Citation